(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Rationale: It is a conceptual-exploratory study that investigates how remote work arrangement and green environmental factors converge and influence work-life balance (WLB) of IT sector employees. This paper explores the interplay between these two rather than them acting on their own to impact employee well-being, productivity and life satisfaction, in the context of the institutionalization of hybrid and remote work and the increased salience of organizational environmental sustainability post-pandemic. The methodology used is non-empirical, literature based approach, the study is synthesis of literature from related studies which are obtained in management literature, environmental psychology, organizational behaviour and human resource management. A narrative-thematic review approach is used to summarise the literature by highlighting recurring constructs, gaps in theory and patterns that emerge from the studies in peer-reviewed journals, industry reports and policy documents (2019–2026) which culminate in the proposed ECOFLEX Framework. Synthesis: Remote work autonomy with access to a green/biophilic environment (home gardens, natural light and low-pollution surroundings) leads to compounding positive effects on WLB which is greater than the effects of either autonomy alone or access to a green/biophilic environment alone. Without access to green spaces, on the other hand, remote working can increase the sense of isolation and lack of boundaries. Implications: Findings provide IT organisations with a foundation for rethinking their remote work practices by adding environmental wellness elements (green workspace allowances, biophilic design guidelines, sustainability related flexibility). Policymakers could think about urban planning and housing aspects of the expanding remote IT workforce. Limitations: This paper is a conceptual study and does not include primary empirical evidence; the proposed ECOFLEX framework needs to be quantitatively and qualitatively tested with further research in various IT organizational settings and across different geographies. Contribution & Novelty: The originality of the study consists of considering the inter-action between the influence of remote work and green environmental variables on WLB, in a manner that was not touched by previous studies, which have mostly considered them as separate antecedents. The ECOFLEX framework is a new integrative lens for future empirical investigation. This article will be relevant to keywords such as Remote Work, Green Environment, Work-Life Balance, IT Sector, Sustainable Workplace Practices.